CAPITAL GAINS AND LOSSES IN ACCOUNTING. - Smith, Kenneth L. (The Accounting Review, 1939)
Abstract This article presents information on capital gains and losses in accounting. Capital gain has been defined as "profit upon realization of assets otherwise than in the ordinary course of business, this profit being the excess of the proceeds of realization over the cost of the property realized." Accounting makes a careful distinction between realized and unrealized capital increments, the latter generally being designated "appreciation." No matter how capital gain is defined the most significant feature of the transaction is that it does not occur in the ordinary course of business. Another peculiarity of capital gain from the accounting point of view is that it is not recognized until actually realized. The conditions and circumstances which bring about capital losses (realized or unrealized) are various. A change in price levels may be a cause. Obsolescence is frequently associated with capital losses. In the case of security investments, factors related solely to market conditions may be primarily influential. To say that capital losses are always non-recurring and outside the regular fulfillment of the particular function of a business enterprise is hardly accurate because obsolescence and many of the other risks which might result in loss of capital are always present and cannot be disassociated from the purposes of an enterprise.